Uncooled Microwave Ablation as a Treatment Option to Preserve Thyroid Function in Patients with Benign Thyroid Nodules - Gulsah Yildirim; Hakki Muammer Karakas (Journal of the Belgian Society of Radiology, 2022)
Objective: The objective is to evaluate the long-term efficacy and safety of uncooled MWA for the treatment of benign thyroid nodules and its long-term effect on thyroid functions. Material and Methods: The study was conducted on 40 patients with 40 nodules. They were treated between September 2019 and December 2020. Nodules’ volumes, thyroid functions (triiodothyronine, free thyroxine, thyrotropin) and anti-thyroid peroxidase and anti-thyroglobulin antibodies were measured before treatment and at 3rd, 6th and 12th month following the treatment. Volume reduction rates and changes in clinical findings were evaluated. Results: The mean volume reduction rate was 49.88, 65.3, and 79.06% at 3rd, 6th, and 12th month, respectively. Antibody levels and thyroid function tests have remained within normal limits and were not exhibited significant change during follow-ups (p > 0.05), except for a significant increase in free thyroxin level at 12th-month (p = 0.007). Subjective symptoms and cosmetic scores were significantly improved all follow-up (p < 0.0001). The only complication was a first-degree skin burn in a patient. Conclusion: In conclusion, uncooled microwave ablation is an effective and safe method for the treatment of benign thyroid nodules and preserves thyroid function.